Watch me - McClintock, Norah (Orca currents, 2008)
Kaz, angry all the time since he was scarred in an accident and his parents divorced, finds life spiraling out of control when he accidently knocks an elderly lady over in the park and then makes the irrational decision to steal her purse rather than help her up.